Relations of the Institute of Roman Studies with the Baltic States (1936–⁠1940) - Kazimierėnas, Arnoldas (Lietuvos istorijos studijos, 2025)
This article explores the cultural diplomacy and ideological outreach of the Institute of Roman Studies (Istituto di Studi Romani) toward the Baltic States, Lithuania, Latvia, and Estonia, during the late 1930s. Founded in 1925 in Fascist Italy, the Institute promoted Romanità, or the ideal of Roman cultural continuity, and aimed to make Latin a revived international scholarly language. Using archival documents, the study details how the Institute pursued connections in the Baltics through diplomatic channels, university partnerships, and direct correspondence with local scholars. While geopolitical upheaval and the onset of World War II curtailed these efforts, the article situates them within the broader strategies of Italian soft power and the transnational intellectual history of classical studies. It also suggests that, absent war and occupation, classical philology in the Baltic region might have developed along very different trajectories.
Keywords: Institute of Roman Studies; Baltic States; cultural diplomacy; classical philology; Latin revival; Italy–Baltic relations